Controllable Synthesis of a Highly Ordered Polymeric Structure Assembled from Cobalt‐Cluster‐based Racemic Supramolecules. Issue 15 (18th July 2018) - Mai, Hien Duy; Lee, Inme; Yoo, Hyojong
Abstract: Metallosupramolecule‐based polymeric platforms with high degrees of hierarchy and tailorable functionalities are of great interests because of their unique morphologies and potential applications. Herein, the controllable synthesis of a highly‐ordered polymeric structure, {[ M, P ‐Co8 (PDA)6 (HIP)3 (DMF)5 (H2 O)]3 ‐[Co(DMF)(H2 O)2 ]} (1 ) (PDA=2, 6‐pyridinedicarboxylate, HIP=5‐hydroxyisophthalate, DMF=dimethylformamide) with unique topology is reported. The solid‐state structure of1 reveals that it is alternately and periodically assembled from racemic supramolecular monomers to form a zigzag‐shaped polymeric strand. Discrete racemic supramolecules (2 ) with topologies similar to those of monomeric species of1 are also controllably synthesized in a separate reaction. Formation of intermolecular hydrogen bonds between supramolecules associated with hydroxyl groups of HIPs are critical for the unique solid‐state packing geometries of1 and2 . Abstract : Tailorable functionalities : A highly‐ordered polymeric structure assembled from a racemic metallosupramolecule is controllably synthesized and fully characterized.